2020
DOI: 10.3201/eid2601.180870
|View full text |Cite
|
Sign up to set email alerts
|

Geographic Distribution and Incidence of Melioidosis, Panama1

Abstract: Melioidosis is an infection caused by Burkholderia pseudomallei. Most cases occur in Southeast Asia and northern Australia; <100 cases have been reported in the Americas. We conducted a retrospective study and identified 12 melioidosis cases in Panama during 2007–2017, suggesting possible endemicity and increased need for surveillance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…15 articles, with a total of 29 patients were excluded due to insufficient clinical information (n = 12) [ 1 , 3 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ] or no report of microbiological diagnosis (n = 3) [ 21 , 22 , 23 ]. A total of 31 articles [ 5 , 10 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ] with 41 patients met the inclusion criteria of this systematic review. We did not exclude articles based on language, although only English-language articles were identified by our search strategy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…15 articles, with a total of 29 patients were excluded due to insufficient clinical information (n = 12) [ 1 , 3 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ] or no report of microbiological diagnosis (n = 3) [ 21 , 22 , 23 ]. A total of 31 articles [ 5 , 10 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ] with 41 patients met the inclusion criteria of this systematic review. We did not exclude articles based on language, although only English-language articles were identified by our search strategy.…”
Section: Resultsmentioning
confidence: 99%
“…Whitmore was the first to describe endocarditis in melioidosis in 1913, reporting a 39–year–old male with small left-sided valvular vegetations post-mortem. In our systematic review, there were 11 patients with endocarditis reported in the literature [ 1 , 5 , 17 , 19 , 24 , 25 , 26 , 27 , 28 ]; six had adequate data for inclusion [ 5 , 24 , 25 , 26 , 27 , 28 ]. All six patients were males with an age range between 29 to 73 years and a mean age of 55.7 years.…”
Section: Resultsmentioning
confidence: 99%
“…The worldwide incidence of melioidosis is unclear likely due to underrecognition and the lack of diagnostic resources in rural areas where the disease is prevalent [ 2 ]. Sporadic cases have been reported all over the globe, and <100 acquired cases were reported in the Americas from 1947 to 2015 [ 6 ]. Twelve melioidosis cases were identified in Panama between 2007 and 2017, but no prostate involvement was described [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, primary prostatic melioidosis cases have been rarely reported among tourists returning from endemic areas in Southeast Asia [ 4 , 5 ]. However, no prior cases of primary prostatic melioidosis have been reported from Panama [ 6 ]. We present a case of primary prostatic abscess due to B pseudomallei in a traveler returning from Panama.…”
mentioning
confidence: 99%
“…19 The same holds true for Panama, 12 cases were identified between 2007 and 2017, suggesting possible endemicity and increased need for surveillance although it has to be mentioned that numbers are low. 20 From the published literature alone, a review recently reported 63 cases of melioidosis from Mexico, central America, and the Caribbean, establishing its endemicity within the region. 21 An excellent example of uncovering the hidden burden using increased surveillance, awareness, and WHO's laboratory capacity building program is that from Sri Lanka.…”
Section: Global Burdenmentioning
confidence: 99%